Students’ Need Analysis in the Content of English for Hotel Accommodation of Vocational High School - Kurniawati, Kadek Lina (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
Different students’ need in vocational high school   with senior high school direct the teachers to analyze the needs of the students in order to design an appropriate teaching-learning activity. The students’ need is emphasized to produce professional students to work in line with their particular field as the aim of vocational high school. The aim of this study was to identify some factual information about the students’ need in English learning, especially in the fourth English language skills, namely listening, speaking, reading, and writing as well as the components of English, namely grammar, vocabulary, and pronunciation. The subject in this study were the tenth-grade students of hotel accommodation program in SMK N 2 Singaraja especially class XP 1 and XP 2. Questionnaire and interview were used to collect the data in this study. The results showed that the students’ need is to meet their own academic professions and their future needs. It was done by covering everyday language of hotel’s activity with its language structure and examples which portray real hotel’s activity in each language skill and its components.